Simultaneous differential detection of H5, H7 and H9 subtypes of avian influenza viruses by a triplex fluorescence loop-mediated isothermal amplification assay - Fan, Qing; Xie, Zhixun; Zhao, Junke; Hua, Jun; Wei, You; Li, Xiaofeng; Li, Dan; Luo, Sisi; Li, Meng; Xie, Liji; Zhang, Yanfang; Zhang, Minxiu; et al. (Frontiers in Veterinary Science, 2024)
H5, H7, and H9 are pivotal avian influenza virus (AIV) subtypes that cause substantial economic losses and pose potential threats to public health worldwide. In this study, a novel triplex fluorescence reverse transcription–loop-mediated isothermal amplification (TLAMP) assay was developed in which traditional LAMP techniques were combined with probes for detection. Through this innovative approach, H5, H7, and H9 subtypes of AIV can be simultaneously identified and differentiated, thereby offering crucial technical support for prevention and control efforts. Three primer sets and composite probes were designed based on conserved regions of the haemagglutinin gene for each subtype. The probes were labelled with distinct fluorophores at their 3' ends, which were detached to release the fluorescence signal during the amplification process. The detection results were interpreted based on the colour of the TLAMP products. Then, the reaction conditions were optimized, and three primer sets and probes were combined in the same reaction system, resulting in a TLAMP detection assay for the differential diagnosis of AIV subtypes. Sensitivity testing with in vitro-transcribed RNA revealed that the detection limit of the TLAMP assay was 205 copies per reaction for H5, 360 copies for H7, and 545 copies for H9. The TLAMP assay demonstrated excellent specificity, no cross-reactivity with related avian viruses, and 100% consistency with a previously published quantitative polymerase chain reaction (qPCR) assay. Therefore, due to its simplicity, rapidity, sensitivity, and specificity, this TLAMP assay is suitable for epidemiological investigations and is a valuable tool for detecting and distinguishing H5, H7, and H9 subtypes of AIV in clinical samples.